Maturation changes of hydrocarbons in solid parts of peloids from Serbian spas - catalytic influence of clay minerals - Nikolovski Zlatko; Šajnović Aleksandra; Gajica Gordana; Burazer Nikola; Brčeski Ilija; Dabić Predrag; Jovančićević Branimir (Journal of the Serbian Chemical Society)
The study focused on inspecting the composition of n-alkane, sterane and terpane biomarkers in healing mud (peloid) organic matter in the Rusanda, Bujanovac and Vranje spas. It was assumed that the catalytic influence of minerals on changes in biomarkers could be effectively evaluated based on the distribution of their biolipid and thermodynamically more stable geolipid structural and stereochemical isomers. Quartz, illite, kaolinite, plagioclase, smectite and chlorite were identified in the samples by powder X-ray diffraction. n-Аlkanes, terpanes and steranes were analyzed in the solid parts of the peloids using the gas chromatography–mass spectrometric, GC–MS, technique. In Rusanda and Bujanovac samples, n-alkanes were identified with distributions characteristic of immature sediments. In contrast, distributions of terpanes and steranes are typical for the mature organic matter of old sedimentary formations. It was concluded that the identified clay minerals do not have an obvious catalytic effect on the maturation of n-alkanes. At the same time, the presence of illite, chlorite, and smectite compensated for all other missing factors (heat, pressure and geological time) by catalytic action and, as a result, gave terpanes and steranes with distributions that are characteristic for petroleum, as the most mature form of organic matter in the geosphere.